Faráři učí interpretovat text: exegeze a didaktika literatury - Vojtíšek, Ondřej (Český jazyk a literatura, 2025)
The article examines the publication Divine Stories or Biblical Bizarro, focusing on a) its conceptualization as a textbook and also b) its method of interpreting literary (namely biblical) texts. Furthermore, this analysis serves as a basis for outlining a reflection on the benefits of this (primarily theological) publication for secondary school literature teaching and – more broadly – on the possibilities of enriching literary didactics through biblical didactics.